Polyurethane Foams: Past, Present, and Future - Gama, Nuno V. (Materials (Basel), 2018)
Polymeric foams can be found virtually everywhere due to their advantageous properties compared with counterparts materials. Possibly the most important class of polymeric foams are polyurethane foams (PUFs), as their low density and thermal conductivity combined with their interesting mechanical properties make them excellent thermal and sound insulators, as well as structural and comfort materials. Despite the broad range of applications, the production of PUFs is still highly petroleum-dependent, so this industry must adapt to ever more strict regulations and rigorous consumers. In that sense, the well-established raw materials and process technologies can face a turning point in the near future, due to the need of using renewable raw materials and new process technologies, such as three-dimensional (3D) printing. In this work, the fundamental aspects of the production of PUFs are reviewed, the new challenges that the PUFs industry are expected to confront regarding process methodologies in the near future are outlined, and some alternatives are also presented. Then, the strategies for the improvement of PUFs sustainability, including recycling, and the enhancement of their properties are discussed.